Dr. Puwit Kongchayanun — Deep Plane Facelift — Korat - Kongchayanun, Puwit (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Puwit Kongchayanun, practicing in Korat, Thailand. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003122; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; thailand; korat